Preparation and characterization study of PPEES/chitosan composite membrane crosslinked with tripolyphosphate - Ismail, Ahmad Fauzi (Elsevier, 2014)
A novel composite membrane was prepared using chitosan (CH) as the active layer supported on a Poly(1,4-phenylene ether ether sulfone) (PPEES) membrane. The chitosan layer was ionically cross linked with sodium tripolyphosphate (TPP). The composite nature of PPEES/CH membranes was confirmed by Scanning Electron Microscopy (SEM). Infrared (IR) spectroscopy results and SEM-EDX analysis confirmed the crosslinking of chitosan surface with TPP. The membranes exhibited higher crosslinking density in acidic media than in basic media. The changes in the hydrophobic nature of PPEES membrane surface due to deposition of chitosan active layer followed by crosslinking were studied by their contact angle measurement, water flux and water uptake studies. The membranes showed rejection up to 55% and 21% towards MgSO4 and NaCl respectively at pH=5 and a flux recovery ratio of 73%.